DIGITAL LIBRARY AS A SOURCE OF STATISTICAL DATA FOR INFORMATIO-ANALYTICAL SUPPORT FOR PEDAGOGICAL STUDIES - O. M. Spirin; T. L. Novytska; A. V. Іatsyshyn (Ìнформаційні технології в освіті, 2018)
In the article we have explored the use of the statistical module IRSTat2 of the digital Library of the National Academy of Sciences of Ukraine in the formation of statistics for the information-analytical support of scientific and pedagogical research. We have described the directions of application of the analytical system Google Analytics as a means of monitoring the use of such a library as a digital educational resource of scientific research support, created on the results of scientific research in the field of pedagogy. There have been considered the peculiarities of monitoring the results of research work and the efficiency of the activity of a scientific institution. A comparative analysis of the Google analytics system and the IRStats2 statistical module has been made. It has been concluded that the analytical system Google Analytics and the statistical module IRSTats2 are expedient to use for scientific and methodological support of digital libraries, management of work on a scientific topic, of a scientific institution, as they allow to form various statistical reports that complement each other and help to determine, how to use the results of research work, in particular digital educational resources, as well as to explore the audience of users and resource authors according to many criteria. They also allow to form both combined and additional statistical reports by introducing additional filtering options.